Precision medicine biomarkers in brain metastases: applications, discordances, and obstacles. (27th November 2021) - Steindl, Ariane; Brastianos, Priscilla K; Preusser, Matthias; Berghoff, Anna S
Abstract: Brain metastases (BM) present a common cause of mortality and morbidity in several metastatic cancer entities. New therapeutic developments during the last decades, including targeted and immune-related therapies, have shown considerable extra- and intracranial response rates in specific subgroups of BM patients. However, differences in the molecular alteration in the BM tumor tissue compared to extracranial tumors leads to heterogeneous therapeutic responses. Therefore, an accurate molecular analyzation of BM tissue, if possible, has become an essential part in therapeutic decision making in BM patients. The concordance of predictive molecular biomarkers between multiple sites including extracranial and intracranial tumor tissue have been analyzed for some but not all biomarkers routinely applied in modern precision medicine approaches. In the present review, we summarize the current evidence of predictive biomarkers for personalized therapy approaches in the treatment of parenchymal BM.